2011
DOI: 10.1017/s1462399411002055
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with curcumin therapy in Alzheimer disease

Abstract: Curcumin, the phytochemical agent in the spice turmeric, which gives Indian curry its yellow colour, is also a traditional Indian medicine. It has been used for millennia as a wound-healing agent and for treating a variety of ailments. The antioxidant, anti-inflammatory, antiproliferative and other properties of curcumin have only recently gained the attention of modern pharmacology. The mechanism of action of curcumin is complex and multifaceted. In part, curcumin acts by activating various cytoprotective pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 105 publications
(123 reference statements)
0
87
0
Order By: Relevance
“…Oxidative damage and inflammatory processes are known to be particularly high in the brains of Alzheimer patients, and as the aqueous extract of turmeric reduces and prevents oxidation, it may be used concurrently in long-term therapy (46)(47)(48)(49).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Oxidative damage and inflammatory processes are known to be particularly high in the brains of Alzheimer patients, and as the aqueous extract of turmeric reduces and prevents oxidation, it may be used concurrently in long-term therapy (46)(47)(48)(49).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In the A␤ 1-42 ELISA kit, anti-A␤ antibodies clone no. BNT77, which detects A␤ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , and clone no. BC05, which detects Cterminus of A␤ , were used.…”
Section: Enzyme-linked Immunosorbent Assay For Amyloid-βmentioning
confidence: 99%
“…Accordingly, the incidence of AD is significantly greater in the US than in India, where curcumin is consumed on a daily basis [19]. However, curcumin is difficult to use as an AD drug because of its poor bioavailability [20]. In contrast with curcumin, PE859 exhibited higher inhibitory activity against the aggregation of both A␤ and tau in vitro, and higher absorption into the blood and penetration of the blood-brain barrier in vivo [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is safe, with little to no toxicity, and possesses antitumor, antioxidant, anti-inflammatory, antiapoptosis, and lipid-reducing pharmacological effects (Motterlini et al, 2000;Ringman et al, 2005;Heneka and O'Banion, 2007). Curcumin has also been used in the prevention and treatment of Alzheimer's disease (AD) (Xiong et al, 2011;Belkacemi et al, 2011;Huang et al, 2012), but the mechanism remains elusive. Epidemiological studies have shown that India has the lowest incidence of AD in the world (Wang and Du, 2003;Perry and Howes, 2011).…”
Section: Introductionmentioning
confidence: 99%